Analisis Interaksi Instrumen Moneter Syariah Terhadap Inflasi dI Indonesia - Ariza, Anggatia (Jurnal Ilmiah Ekonomi Islam, 2024)
Monetary instruments are one tool Bank Indonesia utilizes to try to keep inflation under control. Social wellbeing can be created by stable, low inflation. Because Indonesia has a dual monetary system, both conventional and sharia monetary instruments are used there. The research seeks to ascertain (1) an analysis of the relationship between Indonesian inflation and the Bank Indonesia Sharia Certificate (SBIS). (2) analysis of the relationship between Indonesian inflation and the Mandatory Minimum Reserve (GWM). and 3) an analysis of how Indonesia's inflation is affected by the Bank Indonesia Sharia Savings Facility (FASBIS). This study uses a quantitative methodology and is associative in nature. The research's data analysis method makes use of Vector Autoregression (VAR) analysis techniques, which are run through the Eviews 10 software along with variance decomposition tests and impulse response tests. The results of this research are; 1) SBIS does not have a significant effect on inflation in Indonesia. 2) GWM has a negative effect on inflation but is not significant. 3) Based on the FASBIS variance decomposition test, it has no influence on inflation. The lag test in this research revealed that there is no discernible relationship between Indonesian inflation and the FASBIS variable used to implement sharia monetary operations. The Granger causality test indicates that there is a unidirectional relationship between inflation and FASBIS.